Aloe Vera Gel Accelerated Wound Healing in Oral Mucosa by Reducing Inflammatory Phase (Medical Forum Monthly, 2023)
Objective: The main objective of the study is to find the role of aloe vera gel accelerated wound healing in oral mucosa by reducing inflammatory phase.Study Design: An experimental animal studyPlace and Duration of Study: This study was conducted at the Experimental Research Laboratory of Postgraduate Medical Institute Lahore from June 2019 to December 2019.Materials and Methods: An experimental animal study was conducted at the Experimental Research Laboratory of Postgraduate Medical Institute Lahore to study the histological changes in tongue mucosa wounds at 5th and 7th day post wounding. The therapeutic reagent used in this study was Aloe vera (Aloe barbadensis Miller) gel. Day 5 & 7 pw were selected to see the prolonged effects of the drug on the healing tissue. Study was conducted on 42 albino rats in animal house, Anatomy department, Postgraduate Medical Institute (PGMI), Lahore, Pakistan. In order to detect histological changes, a sample size of 42 albino rats was needed at a significance level of 5% with a Power of the study of 80%, a sample size of 14 in each group was required making a total sample size of 42.Results: Histological observations were made under light microscope after staining the tissues with H & E and IHC stains. Macrophage count, fibroblast count and degree of epithelization were examined by staining tissues with H & E. Angiogenesis was observed by using CD34 IHC stain. Tissue samples from group A1 (control) had incomplete epithelium formation. It was partially covering the ulcer area and was immature with poorly defined epithelial cell layers (figure 1). Granulation tissue had high macrophage count and predominant fibroblasts. Macrophages had a smaller nucleus covered by a larger rim of foamy cytoplasm.Conclusion: Results of the study clearly show that Aloe vera gel accelerates healing in tongue mucosa wounds in Wistar rats. It plays its role by bringing enhanced inflammation, epithelization, angiogenesis and fibrosis. Among the two remedial doses of the gel used in the experiment, the higher dose (500 mg/kg) has proved to be more effective. Aloe vera gel can be used as a remedy to treat oral ulcers.